126 Hypertension and Low Cholesterol as Risk Factors for Infection after Penile Prosthesis Surgery. Issue 1 (1st April 2022) - Loloi, J; Matloubieh, J; Riley, C; Melendez, D; Watts, K; Maria, P
ABSTRACT: Introduction: Erectile Dysfunction (ED) is a common urologic condition affecting a large proportion of men. Typically, first-line treatment consists of oral medications. Inflatable penile prosthesis surgery (IPPS) represents a useful surgical intervention in the treatment of ED, with an estimated 25, 000 IPP procedures performed on a yearly basis in the United States. Infection is a devastating complication of IPPS. The most common risk factors for IPP infection include diabetes, immunocompromised status, and urinary tract infection. Given the significant risk of infection following IPPS, there is an ongoing need to identify contributing risk factors. Objective: We sought to evaluate the association between medical comorbidities, medications, and serum metabolic lab values and infection in our ethnically diverse population. Methods: A retrospective chart review was performed on all men who had primary IPPS between 2017-2019 at our institution. Variables collected include patient demographics, comorbidities, lab values (hemoglobin A1c, testosterone, cholesterol and LDL within 6 months pre-op), and pre-operative urine cultures. Rates of post-operative infection through 60 days and management was also collected. An unpaired t-test (p = 0.05) was used to compare variables between the cohort of men that developed an infection after IPPS surgery and those who did not. Results: 293 men underwent primary IPPS, of whom 14 (4.78%) had post-IPPS infection (Table 1). All patients with an infected prosthesis were treated successfully with antibiotics, penile prosthesis removal and replacement with a malleable prosthesis. The most common organisms obtained from wound cultures were Methicillin-Resistant Staphylococcus Aureus (MRSA), E. coli and normal skin flora. Lower postoperative cholesterol (p=0.024), history of hypertension (HTN) (p=0.026), and anti-lipidemic medications (p=0.039) were significantly different between the infected and non-infected cohorts (Table 2). There was no significant difference between the groups with respect to pre-op hemoglobin A1c and testosterone. Conclusions: IPP is an excellent option for men with refractory ED despite the known risk of infection. In this study, HTN and anti-lipidemic medications were more common in men who developed infection post-IPPS. As HTN can disrupt both macro- and microvasculature over time, it may contribute to poor post-IPPS healing. Despite their potentially beneficial implications in wound healing, statins have been shown to have immunomodulatory effects including inhibition of the immune response, which may make patients more vulnerable to implant infection. It is unclear whether statins' anti-inflammatory properties lead to worse wound healing and impaired ability to fight infection, or whether the fact that patients on anti-cholesterol medications may have worse overall metabolic profile and thus worse wound healing. Further research is needed to confirm these findings and to determine whether maintaining cholesterol within an appropriate range can improve post-IPPS outcomes. Disclosure: No